Menstrual Hygiene Practices Among Adolescent Girls Residing in Tribal and Social Welfare Hostel In Andhra Pradesh: A Community Based Study - Sharvanan E Udayar; Kruthika K; Prasad V Devi (Medsci Publications, 2016)
Introduction: Puberty, which was considered as the time of change for the adolescents, was a challenge for young girls because of menstruation. Though it was a natural phenomenon, various myths surround it, because of which girls will be exposed to very little knowledge about menstruation. This study conducted to know the level of knowledge, attitude and practices during menstruation among the adolescent school girls in rural area. Methodology: The study was among school going adolescent girls residing in tribal social welfare hostels in Kuppam from April to September 2015. Results: The study reported that majority of the girls attained menarche at the age of 13 yrs, and 82.3% are having regular menstrual cycle. Sanitary pads usage during menstruation was seen in 78.5%, and disposal of absorbent was by throwing them into the dust bins in 58.0% people. Mother was the source of information about menstruation before menarche for most of them, and restrictions during menstrual period was seen among almost all of them. Conclusion: Proper knowledge, attitude and hygienic practices in menstruation are not seen among the study subjects, for whom a suitable planned health education, and provision of adequate sanitary facilities was the need of the hour.